(untitled) (Journal of Economic Research & Business Administration, 2023)
The purpose of this study is twofold. First, it is undertaken to assess the current management information systems (MIS) used by the banking sector of Kazakhstan. In addition to that, it is done to come up with a recommendation on how to set up an efficient MIS in the banking industry of Kazakhstan. Due to the rapid development of the financial sector in Kazakhstan, local banks require an efficient MIS to be and stay competitive in the challenging sector. Moreover, future employee resistance should be avoided after the successful implementation of efficient MIS. To ensure the representativeness of the sample size, the questionnaire has been disseminated among 250 employees who face MIS. This research covers the implementation of the right system and managing human factors for its proper functioning over a long period. To evaluate the effectiveness of the MISs used by the banking sector in Kazakhstan, the questionnaire has been designed and disseminated among employees of one of the largest banks in Kazakhstan. This study contributed to the existing literature by investigating MIS in the banking sector of Kazakhstan. The benefits and results of the information systems as well as their significance for the banking sector are discussed and analysed in this study. An efficient MIS sets and provides data that management requires to achieve its goals. The right MIS provides a decision support system which could be the most useful tool for the bank in solving complex questions. The fundamental steps to develop MIS, which should be adopted by the bank have been presented in this study. Keywords: Kazakhstan, MIS, banking industry, operational efficiency